STRUKTUR DAN FUNGSI SOSIAL CERITA RAKYAT LEGENDA ANAK DURHAKA AWANG TIKULUAK DI KANAGARIAN SUNGAI SARIAK KECAMATAN VII KOTO KABUPATEN PADANG PARIAMAN - Sabrina, Imelia; Hasanuddin WS, Hasanuddin WS (Universitas Negeri Padang, 2019)
The study aims to describe: (1) the structure of local legend Awang Tikuluak in Kanagarian Sungai Sariak Sub-district VII Koto District Padang Pariaman, and (2) the social function of local legend Awang Tikuluak in Kanagarian Sungai Sariak Sub-district VII Koto District Padang Pariaman. The source of this research data is story about local legend Awang Tikuluak in Kanagarian Sungai Sariak Sub-district VII Koto District Padang Pariaman. There are four stages to analyze the data. First, data inventory, Second, data classification. Third, conclude the data classification result. Fourth, write the research report. Based on result of the study concluded: (1) The folklore of local legend Awang Tikuluak told by informant with local language, the main character is Saleha, and theme of the story is about rebellious child, and (2) social function of the local legend Awang Tikuluak are for education, cultural preservation, and group identity.Keywords: folklore, structure, social function